Urban Revitalisasi dan Transformasi Perkotaan Kawasan 3T di Kabupaten Jayawijaya: Pendekatan Ekonomi Berkelanjutan Berdasarkan RPJMD Provinsi Papua Pegunungan - YM, Hardiyanti; Faradiba, Andi Astri; Yuniarti, Erni; Wenda, Notiben; Wenda, Endius (Universitas Tanjungpura, 2026)
This analysis calls for revitalizing urban areas and transforming 3T areas in the Regency of Jayawijaya, with an emphasis on economic, social, and environmental aspects. In survey A, a questionnaire administered to 100 respondents found that public awareness of the importance of revitalization for a growing local economy (average score 6.5) and of improving quality of life (average score 6.5) was high. The resulting recommendations encompass sustainable development infrastructure, including durable roads and bridges that withstand rain; the implementation of agricultural programs in a supportive environment with farmer training; and enhanced public participation in planning through community forums. In addition, the importance of system-efficient drainage (average score: 6.75) and collaboration in protecting the environment were identified as crucial to addressing climate change. Government Regency Jayawijaya and the Papua Mountains Province can create more sustainable and prosperous areas, where synergy among economic, social, and environmental aspects serves as the foundation for achieving sustainable development.